Poverty Reduction and Growth Trust : 2018 Borrowing Agreement with the Banque de France. (Policy Papers; Policy Paper ;, 2018)
The Fund, as Trustee of the Poverty Reduction and Growth Trust (PRGT or Trust), has entered into a new borrowing agreement (the 'Agreement') with the Banque de France (hereafter France), effective on February 1, 2018. This new borrowing agreement with France provides new resources to the Extended Credit Facility Loan Account of the PRGT in the total amount of up to SDR 2 billion. Pursuant to Section III, paragraph 2 of the Instrument to establish the PRGT, the Managing Director is authorized to enter into borrowing agreements and agree to their terms and conditions with lenders to the Loan Accounts of the Trust. This paper presents the new Agreement with France to the Executive Board for information. Including this Agreement with France, the Fund has concluded fifteen new PRGT loan agreements providing total resources of SDR 11.4 billion in the context of the 2014 Board endorsed PRGT fundraising with a goal of SDR 11 billion. To accommodate the better-than-expected outcome, and following consultations with PRGT creditors, the IMF Board increased the PRGT's cumulative borrowing limit on January 8, 2018. This is the sixth borrowing agreement between France and the Fund as Trustee of the PRGT. The Agreement incorporates the extensions of the commitments and drawdown period for PRGT loans to end-2020 and end-2024, respectively, consistent with the Fund's framework for concessional lending to low income countries adopted in other PRGT borrowing agreements.